Conditioning requirements in today`s elite juniors - König, D. (2000)
The age at which young tennis players enter the professional tennis circuit has steadily decreased in recent decades. Today, the mean age at which tennis players compete in their first professional tournament is 15 for females and 16.5 for males. Therefore, professional careers are starting while players are still juniors, implying that the physical condition of ambitious tennis juniors should not differ substantially from that of their older opponents. Many studies have shown that among the various fitness parameters, anaerobic alactic motor abilities such as agility, speed, explosiveness, strength and power are best correlated with on-court performance. Fitness tests for the evaluation of these tennis-specific motor skills have been established for both adults and juniors, helping coaches and players to determine which areas of fitness need to be improved. There is, however, evidence that both anaerobic lactic metabolism and aerobic capacity play an important role in success in tennis. Although the overall intensity during a match is sub-maximal (60 - 70 % of VO2max), lactate levels may increase to 5-6 mmol/l during long and fast rallies. It is important that lactate degradation occurs fast, since lactate accumulation is associated with muscular fatigue and reduced accuracy. Therefore, conditioning programmes in tennis should include anaerobic glycolytic training. A 3-fold increase in lipolytic metabolites such as glycerol has been measured in the course of a tennis match. This indicates a considerable amount of oxidative metabolism for energy production in singles tennis. Good aerobic capacity could be a decisive factor for winning, particularly in long and strenuous matches, since an enhanced potential to oxidize fatty acids spares muscle glycogen, reduces lactate accumulation at submaximal intensity and postpones exhaustion. Nevertheless, improved aerobic capacity in tennis should not be realised through long lasting endurance activities. Such training induces a transformation from fast-twitch glycolytic (IIb) to fast-twitch oxidative-glycolytic (IIa) muscle fibres, thus reducing strength, power, speed and explosiveness. Tennis players should therefore follow conditioning programmes that improve both aerobic and anaerobic performance, such as sprint interval training. This type of training has shown to increase both glycolytic and oxidative enzyme activity, maximum short power output and VO2max. In conclusion, the multifaceted fitness requirements in tennis include strength, power, speed, agility, explosiveness and endurance components. The fact that tennis players begin their professional career at age 15 or 16 implies that regular training has to start in childhood. There is a general consensus that during childhood, training programmes that include all-round aerobic conditioning and other types of sport, such as basketball, will best promote a large range of diverse motor skills. An increasing amount of anaerobic and strength components should not be included before the onset of puberty. Anaerobic training at a young age leads to comparatively little improvement in anaerobic capacity, since the enzymes for anaerobic energy metabolism are not fully developed. At the same time, this type of exercise is too strenuous for pre-pubertal boys and girls. Therefore, conditioning in children and juniors should be age-specific and requires a long-term training concept to prevent overstrain, injuries and burnout syndromes.